A novel sleep optimisation programme to improve athletes' well-being and performance - Van Ryswyk, E.; Weeks, R.; Bandick, L.; O'Keefe, M.; Vakulin, A.; Catcheside, P.; Barger, L.; Potter, A.; Poulos, N.; Wallace, J.; Antic, N. A. (European Journal of Sport Science, 2017)
Objectives: To improve well-being and performance indicators in a group of Australian Football League (AFL) players via a six-week sleep optimisation programme. Design: Prospective intervention study following observations suggestive of reduced sleep and excessive daytime sleepiness in an AFL group. Methods: Athletes from the Adelaide Football Club were invited to participate if they had played AFL senior-level football for 1-5 years, or if they had excessive daytime sleepiness (Epworth Sleepiness Scale [ESS] >10), measured via ESS. An initial education session explained normal sleep needs, and how to achieve increased sleep duration and quality. Participants (n = 25) received ongoing feedback on their sleep, and a mid-programme education and feedback session. Sleep duration, quality and related outcomes were measured during week one and at the conclusion of the six-week intervention period using sleep diaries, actigraphy, ESS, Pittsburgh Sleep Quality Index, Profile of Mood States, Training Distress Scale, Perceived Stress Scale and the Psychomotor Vigilance Task. Results: Sleep diaries demonstrated an increase in total sleep time of approximately 20 min (498.8 ± 53.8 to 518.7 ± 34.3; p < .05) and a 2% increase in sleep efficiency (p < 0.05). There was a corresponding increase in vigour (p < 0.001) and decrease in fatigue (p < 0.05). Conclusions: Improvements in measures of sleep efficiency, fatigue and vigour indicate that a sleep optimisation programme may improve athletes` well-being. More research is required into the effects of sleep optimisation on athletic performance.